[en] IS GOD FOR EVERYONE?: TRANSVESTIES, SOCIAL INCLUSION AND RELIGION - LUIZ ALBERTO FARIA RIBEIRO (MAXWELL, 2010)
[pt] O presente estudo tem como objetivo pesquisar a relação entre travestis moradores do Rio de Janeiro e as religiões cristãs, umbanda, candomblé, budista, espírita e wicca. Para isto, foram entrevistadas travestis de diversas idades. Esta pesquisa também procura confirmar quais formas de violência e exclusão são vítimas; além de quais locais e redes sociais estão inseridas, além da pista, pois nesta também sofrem violência física e, em alguns casos, encontram a morte. Este estudo tenta averiguar se o espaço religioso pode ser uma possibilidade em que haja a inclusão das travestis, podendo possibilitar um aumento em sua autoestima. === [en] The aim of the present study is to research the relationship between the transvestites living in Rio de Janeiro and christian, umbanda, candomble, buddhist, spiritualist and wicca religions. In order to achieve this, transvestites from several ages were interviewed. This research also aims to find out the kinds of violence and exclusion they are victims of; discover the places and social networks they belong to, aside from the scope of ‘the streets’, where they also suffer physical violence and, in some cases, meet death. This study tries to find out if religion can be a place in which there is inclusion for the transvestites, making it possible to improve their self-esteem.